Case Report of Posttraumatic Middle Cerebral Artery Territory Infarct - Ajaya Kumar Ayyappan Unnithan (Indian Journal of Neurosurgery)
Abstract A 27-year-old man had severe diffuse brain injury. The patient developed malignant right MCA territory infarction on second day. Emergency decompressive craniectomy was done. He was ventilated. He developed subdural hygroma on the opposite side that was drained. He improved slowly. He had hydrocephalus. VP shunt was done. He became conscious but dependent. PEG was done for feeding. Cranioplasty was done for syndrome of trephined. The patent improved to a state of good cognition with residual motor aphasia and left hemiplegia. Posttraumatic cerebral infarction is an indicator of poor prognosis. Vasospasm, intimal dissection, and thrombosis are the mechanisms. MCA territorial infarction is rare. Usual mechanism is impact of rotational forces on relatively fixed M1 segment on the posterior margin of lower wing of sphenoid, resulting in arterial dissection or intimal damage.